Pengembangan Sistem Pelayanan Administrasi Kependudukan Desa berbasis Web (Studi Kasus: Desa Talok) - Hegi Restu Alegretto; Tri Astoto Kurniawan (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2021)
Demographic administration is a method used to document the results of demographic registration and civil registration. In registering the demography, Talok Village still uses a manual method by book or file records. This type of demographic registration is ineffective since it will cause unnecessary effort in case of information changes because the village staffs have to look for the file records manually. Talok Village also provides services of the issuance of several residence certificates and identity cards. However, residents find it difficult to apply for residence certificates and identity cards due to the lack of information. A web-based demographic administration service system was developed to overcome these problems. This system used the waterfall model and object-oriented approach and had been tested using the unit, integration, and validation testings. The unit and integration testings were conducted using the whitebox testing technique and resulting valid results. Meanwhile, the validation testing was conducted using the blackbox testing technique and resulting valid result. The result of this research is a web-based demographic administration service system.